Results of a 2-Week Inpatient Stay at the Department for Internal and Integrative Medicine: An Observational Study. (24th October 2012) - Lauche, Romy; Cramer, Holger; Moebus, Susanne; Paul, Anna; Michalsen, Andreas; Langhorst, Jost; Dobos, Gustav
Abstract : Introduction . The Department for Internal and Integrative Medicine in Essen utilizes mind/body medical elements in order to empower patients with chronic diseases to better cope with their symptoms and to adopt a healthy lifestyle. This study explored the influence and predictors of a 2-week integrative treatment program on patients' quality of life. Methods . This observational study was conducted with inpatients as part of the quality assurance program. Patients' quality of life, psychological symptoms, and health locus of control were measured on admission and discharge and again 3, 6, and 12 months after discharge. Regression analyses were conducted to determine the factors predicting improved quality of life. Results . Data from 2486 inpatients treated in 2001–2004 were included (80% female, mean age 53.9 ± 14.3 years). Response rates decreased to 50% at 12 months. Small-to-moderate effects were found on patients' quality of life, anxiety, and depression. Patients' internal locus of control significantly increased. Improved quality of life was mainly predicted by lower baseline scores. Conclusion . Results of this study suggest that a 2-week inpatient treatment might sustainably reduce patients' symptoms and increase their quality of life; however, conclusions are only preliminary. More research is needed to enable the effectiveness to be judged conclusively.